Language Change in a Contact Situation: The Case of Slovene in North America - Šabec, Nada (Slovenski jezik / Slovene Linguistic Studies, 2025)
The article discusses the linguistic situation among immigrants of Slovene descent in the United States of America and Canada. Owing to the geographic distance between Slovenia and the host country and particularly to the very strong influence of the pragmatically dominant English, Slovene there is undergoing a very specific kind of development. Data collected through empirical research (interview excerpts) are analyzed in order to identify contact-motivated changes of Slovene. These are encountered in all types of bilingual discourse (borrowing, code switching, English-influenced monolingual Slovene) and on different linguistic levels from phonology to semantics and pragmatics. The most salient areas of English linguistic impact, however, are morphology with its simplification, regularization and/or even deletion of Slovene inflectional system, and syntax with its gradual adoption of English-like SVO word order patterns. On a sentence level these kinds of structures constitute what could be termed a composite matrix language, made up from the features of both languages. Development, though, stops short of the so-called matrix language turnover (MLT), because it is interrupted by a very rapid process of language shift from Slovene to English. This has been accomplished in the course of three generations in the case of pre-war immigrants and even faster in the case of post-war ones. The variety of Slovene in this particular context is therefore of a very temporary and unstable nature and defies the postulation of rigid structural constraints on it. It nevertheless represents a distinct contact variety of Slovene well worth further research because of the likely insights into the language change mechanisms that it may provide.